The ten commandments of lean six sigma : a guide for practitioners - Antony, Jiju; Sunder, Vijaya M.; Laux, Chad; Cudney, Elizabeth (Bingley, U.K. : Emerald Publishing Limited, 2019)
Presented from the perspective of practitioners, researchers and academics, The Ten Commandments of Lean Six Sigma serves as a practical guide for senior managers and executives who want to achieve operational and service excellence in various manufacturing, service and public sector organization.
Prelims -- Chapter 1 Introduction to Lean Six Sigma and Ten Commandments -- Chapter 2 Alignment of Lean Six Sigma with Organisational Strategy -- Chapter 3 Lean Six Sigma Project Selection and Prioritisation -- Chapter 4 Selecting Top Talent for Execution of Projects -- Charter 5 Leadership for Lean Six Sigma Deployment -- Chapter 6 Effective Training and Design of Curriculum for Different LSS Roles -- Chapter 7 Development of Rewards and Recognitions for LSS -- Chapter 8 Lean Six Sigma Sustainability -- Chapter 9 Linking Lean Six Sigma with Innovation and Organisational Learning -- Chapter 10 Linking Lean Six Sigma with Green and Environmental Sustainability -- Chapter 11 Beyond LSS: Emerging Themes of Lean Six Sigma -- References -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Six sigma (Quality control standard); Industrial efficiency; Business & Economics, Production & Operations Management; Production & quality control management